Development of Household Income Towards Modern Welfare Economics in Latvia - Sloka, Biruta; Tora, Ginta; Buligina, Ilze; Dzelme, Juris (My University, 2020)
Latvia in international comparisons is among the countries with rather low average income for households but rather high differences in income in households, especially in highest income households (richest quintile) characterised with significant indicators of variability in euro zone countries by Household and Consumption Survey conducted buy Bank of Latvia by methodology of European Central Bank in all eurozone countries and according EU- SILC (European Union Statistics on Income and Living Conditions) data. This current research is devoted to analysis of development of income and variability of income of households in Latvia in comparison with other OECD countries and eurozone countries. Research methods used: scientific publications and previous conducted research analysis, analysis of Household and Consumption Survey data, EU-SILC data on differences in income depending household size, from regions and from territory (urban/rural), interviews of regional authorities on various income inequality reduction arrangements and applications in regions with lower income level. Data analysis methods: descriptive statistics (indicators of central tendency or location – arithmetic mean and median, indicators of variability – standard deviations, standard error of mean), cross-tabulations of household income by regions, by household size, by territories, testing of statistical hypotheses on differences of arithmetic means by analysis of variance (ANOVA) for significance of income differences by regions and by household size. Results of analysis has indicated that Latvia has significant challenges where several innovative approaches could be applied to find best solutions for income inequality decrease and increase of overall satisfaction with life and support for economic development of the country.
Keywords: EU-SILC; Household size; Income differences; Labour Force Survey; Regions; Research Subject Categories::SOCIAL SCIENCES::Business and economics